On the taxonomy and natural history of the secretive Ischnocnema lactea Miranda-Ribeiro, 1923) (Anura: Brachycephaloidea: Brachycephalidae) - Silva-Soares, Thiago; Malagoli, Leo Ramos; Cruz, Carlos Alberto Gonçalves; Caramaschi, Ulisses (Zootaxa, 2018)
The original description of Ischnocnema lactea (Miranda-Ribeiro, 1923) was based on two specimens and an inaccurate type locality. These circumstances have obscured the identity of this name. Moreover, the I. lactea species has had a complex taxonomic history and, in general, specimens of species in this group are poorly represented in amphibian collections. The diagnosis of the series is confusing, with many non-exclusive and variable characters barely useful. An accurate diagnosis for the series requires a precise characterization of I. lactea, its type species. Recently discovered populations, museum data, and new information on the collector of the type specimen allowed the elucidation of important issues related to this species. Here we provide the redescription of Ischnocnema lactea based on the lectotype, and intraspecific variation based on newly collected specimens. Ischnocnema lactea is characterized by its large body size (adult 19.6–26.7 mm SVL; females 27.6–34.3 mm SVL); dorsum and flanks rugose, venter granular; vocal sac single and subgular, externally expanded; finger disks expanded, T-shaped, indented and truncate in fingers II–IV; toes relative length I<II<III<V<IV; black blotch on cloacal region, tarsus, and feet; moderate calcar tubercle present. Its advertisement call consists on a single short pulsed note ranging from 634 to 1060 milliseconds, with dominant frequency ranging from 2239.5 to 2756.2 Hz. Males call perched on vegetation mostly during daytime, starting early in the morning, and reproduction is explosive, associated to cold front rains. Ischnocnema lactea is a secretive and endemic inhabitant of the Serra do Mar in Southeastern Brazil. The type locality is redefined to the Municipality of Caraguatatuba.